2016
DOI: 10.2196/resprot.5061
|View full text |Cite
|
Sign up to set email alerts
|

Online Tobacco Cessation Training and Competency Assessment for Complementary and Alternative Medicine (CAM) Practitioners: Protocol for the CAM Reach Web Study

Abstract: BackgroundComplementary and alternative medicine (CAM) practitioners, such as chiropractors, acupuncturists, and massage therapists, are a growing presence in the US health care landscape and already provide health and wellness care to significant numbers of patients who use tobacco. For decades, conventional biomedical practitioners have received training to provide evidence-based tobacco cessation brief interventions (BIs) and referrals to cessation services as part of routine clinical care, whereas CAM prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…A search of MT training on PubMed and Google Scholar revealed that most articles focus on massage therapy as an intervention and the health outcomes of massage. Few scholarly articles addressed training MTs for a specific skill following their primary professional education [15,16]. Muramoto et al [16] were the first to successfully develop and implement e-training (BBI training and competency evaluation) of complementary and alternative medicine providers (including MTs) for screening clients for tobacco use and encouraging tobacco cessation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A search of MT training on PubMed and Google Scholar revealed that most articles focus on massage therapy as an intervention and the health outcomes of massage. Few scholarly articles addressed training MTs for a specific skill following their primary professional education [15,16]. Muramoto et al [16] were the first to successfully develop and implement e-training (BBI training and competency evaluation) of complementary and alternative medicine providers (including MTs) for screening clients for tobacco use and encouraging tobacco cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Guided by our conceptual framework and formative data collection, we adapted content from 2 existing Web-based training programs: (1) a multimedia skin cancer risk reduction academic course, currently tailored for university students in the health sciences [20] and (2) MT client-centered communication and referral skills modules used in a BBI training for tobacco cessation [16].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations